2022
DOI: 10.1111/dth.15294
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling combined with pimecrolimus, 5‐fluorouracil, and trichloroacetic acid in the treatment of vitiligo: A comparative study

Abstract: Treatment of vitiligo represents a highly therapeutic challenge in spite of the continuous development of new modalities. Combination therapies of vitiligo can help improve treatment response, and reduce recurrence potential. To compare the efficacy and adverse effects of microneedling combined with-fluorouracil, pimecrolimus, and trichloroacetic acid (TCA) in the treatment of localized, stable vitiligo. The study included 75 patients with non-segmental, stable vitiligo who were randomly assigned to three equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In recent years, with the continuous improvement of the medical level, microneedle therapy has been gradually known and widely used in the medical field. Nofal et al [30] found that the microneedle had the characteristics and advantages of precisely adjustable depth and realtime monitoring, and the depth and energy of the micro-needle could be adjusted according to the different degrees by penetrating the skin with the microneedle. The tip of the microneedle penetrated the skin to introduce drugs, which not only improved the utilization value of drugs to achieve the effect of targeted therapy but also effectively avoided epidermal stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the continuous improvement of the medical level, microneedle therapy has been gradually known and widely used in the medical field. Nofal et al [30] found that the microneedle had the characteristics and advantages of precisely adjustable depth and realtime monitoring, and the depth and energy of the micro-needle could be adjusted according to the different degrees by penetrating the skin with the microneedle. The tip of the microneedle penetrated the skin to introduce drugs, which not only improved the utilization value of drugs to achieve the effect of targeted therapy but also effectively avoided epidermal stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Group B streptococcus is a common pathogen, mainly infecting pregnant women and newborns, which may lead to maternal and infant infection, premature delivery, and even death. Therefore, timely use of antibiotics in the perinatal period can effectively inhibit and kill pathogens such as GBS and reduce the risk of maternal and infant infection [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding reported efficacy, Nofal et al [63] published a 100-patient study reporting an 80% response rate in eyelid vitiligo, with a lower response rate in the face, torso and extremities with the application of variable concentrations of TCA every 2 weeks for 12 months. Two studies investigated the combination of microneedling and TCA, interestingly finding better response rates with the application of 70% TCA [65] than with 100% TCA [66]. The single application of 15% TCA in combination with NB-UVB achieved an excellent response in 70% of patients in a clinical trial [67].…”
Section: Trichloroacetic Acid (Tca)mentioning
confidence: 99%